Torrefaction of Maize Residue Pellets with Dry Flue Gas - Thossaporn Onsree (2020)
© 2019, Springer Science+Business Media, LLC, part of Springer Nature. In this work, maize residue pellets were torrefied in a macro thermogravimetric analyzer with simulated dry flue gas from mixing of CO2 and N2. The effects of temperature (220–300 °C), residence time (10–40 min), and the presence of CO2 (0–18% v/v) in the reacting gas were investigated on products’ yields, distribution, and torrefied pellet properties such as higher heating value (HHV), elemental composition (C, H, O, N, S, K, and Cl), grindability, and moisture uptake ability. Temperature and residence time were found to affect the distribution of products’ yield and the properties of torrefied pellets considerably. In comparison with the untreated biomass pellets, the torrefied pellets appeared to have improved HHV and grindability but reduced moisture uptake ability. In the presence of CO2, the Boudouard reaction caused slight reductions in the C content and HHV of the torrefied pellets. Changes in torrefaction conditions did not prove to have a statistically significant effect on S, K, and Cl contents of the torrefied biomass materials.